Evaluation of Energy Consumption and Carbon Dioxide Emission from a Solar / Gas Powered Absorption Air Conditioning System in Zaria - Ahmadu, T. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Electrically powered vapour compression chillers consume high power and make use of synthetic refrigerants which when released have negative effect on the environment. In this study, the energy consumption and carbon dioxide (CO2) emission from an absorption air conditioning system were evaluated. The experimental scale absorption air conditioning system has its thermal energy requirement supplied by the solar collector system and liquefied petroleum gas. The air conditioning system was operated for ten experimental days, in both solar and gas heating modes. Daily power consumption by the system was measured. The daily CO2 emitted by the system was evaluated using the daily gas consumption. These were compared to electric power consumption and GWP from conventional chillers of varying energy efficiency ratio (EER). Results showed that the absorption cooling system has reduced power consumption in the range of 31.5% to 64.2% as compared to conventional vapour compression chiller of varying EER. Also, CO2 emission was seen to have been reduced. This reduction was within the range of 13.3% to 43.2% when compared to that from conventional vapour compression chiller of low to average EER.